Interpretation of Lengkara's Depression in the Novel 00.00 by Ameylia Falensia: Cognitive Triad Theory - Neng Ayu Wulandari; Abdul Kholiq (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe the forms of emotion and depression experienced by the character Lengkara in the novel 00.00 by Ameylia Falensia using Beck’s Cognitive Triad approach. The research was conducted in 2024 employing a descriptive qualitative method. The data source consisted of the printed and digital versions of the novel 00.00. Data were collected through reading and note-taking techniques, while the data analysis referred to Miles and Huberman’s model, including data reduction, data display, and conclusion drawing. The research instrument was the researcher herself, supported by a categorization table of emotions and cognitive triad indicators. The findings show that Lengkara experiences various negative emotions, such as fear, sadness, anger, disappointment, hopelessness, and recurrent psychological pressure. Based on Beck’s Cognitive Triad, Lengkara’s depression is reflected in three main aspects: negative view of self, negative view of the world, and negative view of the future. Lengkara tends to blame herself, perceive herself as worthless, view her environment as emotionally threatening, and believe that her future holds no hope. These results indicate that the novel 00.00 presents a complex representation of depression relevant to the psychological dynamics of modern adolescents. This study contributes to literary psychology research, particularly in understanding character cognitive distortions through the Cognitive Triad theory.